The Codes of the Street in Risky Neighborhoods A Cross-Cultural Comparison of Youth Violence in Germany, Pakistan, and South Africa - Heitmeyer, Wilhelm (Springer Nature, 2019)
This book presents a comparative look at the norms and attitudes related to youth violence. It aims to present a perspective outside of the typical Western context, through case studies comparing a developed / Western democracy (Germany), a country with a history of institutionalized violence (South Africa), and an emerging democracy that has experienced heavy terrorism (Pakistan). Building on earlier works, the research presented in this innovative volume provides new insights into the sociocultural context for shaping both young people's tolerance of and involvement in violence, depending on their environment. This volume covers: Research on interpersonal violence. Thorough review of the contribution of research on gangs, violence, neighborhoods and community. Analyses on violence-related norms of male juveniles (ages 16-21 years old) living in high-risk urban neighborhoods. Intense discussion of the concept of street code and its use. Application of street code concept to contexts outside the US. An integrating chapter focused on where the street code exists, and how it is modified or interpreted by young men. With a foreword by Jeffrey Ian Ross, this book aims to provide a broader context for research. It does so via a rigorous comparative methodology, presenting a framework that may be applied to future studies. This open access book will be of interest to researchers in criminology and criminal justice, as well as related fields such as sociology, demography, psychology, and public health.